Effects of terrorism on international tourism from the perspective of behavioural economics - Havlíčková, Blanka; Abrhám, Josef; Wawrosz, Petr; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2018)
The impact of terrorism on international tourism has been studied many times. This thesis deals with this issue from a new perspective of behavioral economics, which emphasizes cognitive distortions in human decision-making. The aim of the thesis was to theoretically map out the cognitive distortions in human decision-making connected with the impact of terrorism on international tourism, whether on consumers/visitors of tourist destinations, operators or public authorities. This thesis presents in total nineteen cognitive distortions and also delineates their practical implications. This work also tries to find out if the presence of armed soldiers and policemen in tourist centers increases or decreases the subjective risk perception of a terrorist attack and also whether the presence of these armed forces in front of the tourist attraction reflects the willingness of tourists to visit the tourist attraction and spend more on the admission fee. For this purpose, this dissertation thesis presents researches based on behavioral method with setting in Prague, Paris and Jerusalem, involving a total of 3000 respondents. The main finding of this dissertation thesis is that the subjective risk perception of terrorism in the presence of armed soldiers is influenced by the prevalence of chronic anxiety and/or chronic depression. The findings of this dissertation may be useful for public authorities who decide on the location of the armed forces in city centers.
Vedoucí práce: Josef Abrhám
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor disert. práce]; disertace; dissertations